2021
DOI: 10.21203/rs.3.rs-124634/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

ACE2-like carboxypeptidase B38-CAP protects from SARS-CoV-2-induced lung injury

Abstract: Angiotensin-converting enzyme 2 (ACE2) is a receptor for cell entry of SARS-CoV-2, and recombinant soluble ACE2 protein inhibits SARS-CoV-2 infection as a decoy. ACE2 is the carboxypeptidase to degrade angiotensin II (Ang II) to angiotensin 1-7 and improves the pathologies of cardiovascular disease and acute lung injury. To address whether the carboxypeptidase enzymatic activity of ACE2 is protective against COVID-19, we investigated the effects of B38-CAP, an ACE2-like enzyme, on SARS-CoV-2-induced lung injur… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 51 publications
0
5
0
1
Order By: Relevance
“…Multiple studies confirm the beneficial effect of ACE2 enzymatic activity in anti–SARS-CoV-2 activities of the ACE2–based therapeutics ( 11 , 59 ). Active sACE2 and ACE2-like enzymes were shown to effectively reduce the vasopressor Ang II in plasma and attenuate acute lung injury caused by SARS-CoV-1 and SARS-CoV-2 by rebalancing renin-angiotensin homeostasis when membrane-bound ACE2 has been stripped and down-regulated by S binding ( 11 , 12 , 42 ). Thus, compared to inactive forms, engineered ACE2 antivirals with intrinsic Ang II–converting activity are expected to be a better therapeutic option, which can not only block viral spread but also modulate the RAS system to prevent lung failure in patients with SARS-CoV-2.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Multiple studies confirm the beneficial effect of ACE2 enzymatic activity in anti–SARS-CoV-2 activities of the ACE2–based therapeutics ( 11 , 59 ). Active sACE2 and ACE2-like enzymes were shown to effectively reduce the vasopressor Ang II in plasma and attenuate acute lung injury caused by SARS-CoV-1 and SARS-CoV-2 by rebalancing renin-angiotensin homeostasis when membrane-bound ACE2 has been stripped and down-regulated by S binding ( 11 , 12 , 42 ). Thus, compared to inactive forms, engineered ACE2 antivirals with intrinsic Ang II–converting activity are expected to be a better therapeutic option, which can not only block viral spread but also modulate the RAS system to prevent lung failure in patients with SARS-CoV-2.…”
Section: Discussionmentioning
confidence: 94%
“…Multiple studies confirm the beneficial effect of ACE2 enzymatic activity in anti–SARS-CoV-2 activities of the ACE2–based therapeutics ( 11 , 59 ). Active sACE2 and ACE2-like enzymes were shown to effectively reduce the vasopressor Ang II in plasma and attenuate acute lung injury caused by SARS-CoV-1 and SARS-CoV-2 by rebalancing renin-angiotensin homeostasis when membrane-bound ACE2 has been stripped and down-regulated by S binding ( 11 , 12 , 42 ).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Interestingly, expression of ACE2 and its enzymatic activity is decreased in SARS-CoV and inflammatory conditions ( Guy et al, 1992 , Kuba et al, 2005 , Sodhi et al, 2018 ) and hence one may speculate that the interaction of SARS-CoV-2 with ACE2 may impair the function of ACE2 leading to a relative abundance of active bradykinin metabolites with subsequent B1 receptor activation, local pulmonary edema and exacerbated lung injury ( Sodhi et al, 2018 ). Indeed, a reduced ACE2 expression in hamster lungs after SARS-CoV-2 infection was recently demonstrated ( Yamaguchi et al, 2021 ). In a recently published study, a soluble ACE2 protein with increased binding to the spike protein has shown protective capabilities with regards to lung and kidney injury ( Hassler et al, 2022 ).…”
Section: The Role Of the Contact Activation And Kallikrein-kinin Syst...mentioning
confidence: 99%
“…Говоря о терапии статинами, следует отметить, что, с одной стороны, статины повышают экспрес- Вирус SARS-CoV-2 проникает в дыхательные пути и связывается с клеткой мишенью (альвеолярные клетки 2 типа), имеющие рецепторы ангиотензинпревращающего фермента II типа (ACE2) [1]. Гипотеза о причастности ренин-ангиотензиновой системы к воспалительному процессу, спровоцированному проникновением SARS-CoV-2 в ткани (в первую очередь в легкие), учитывает, что потеря функции ACE2 вызывает дисбаланс, повышая концентрацию ангиотензина II в тканях (провоспалительный эффект) и одновременно снижая уровень ангиотензина 1-7 (противовоспалительное действие) [2,3]. Это приводит к высвобождению провоспалительных цитокинов [4,5]…”
Section: оптимизация контроля артериального давления органопротекции ...unclassified